Use of Dreams in Girish Karnad’s The Dreams of Tipu Sultan (Global Journal of Human-Social Science, 2018)
Girish karnad s in his play the The Dreams of Tipu Sultan use the concept of dreams to indicate the downfall of Tipu Sultan through his dreams The dreams of Tipu Sultan can be interpreted as symbol or an indication which focuses on his downfall in the future The dreams book Khwab-nama was looted from Seringapatam along with other books The book was not in library or the royal library in Seringapatam It was discovered hidden in the bed chamber of Tipu Sultan palace Lal Mahal the ruin of which can be seen today in front of the Sri Ranganatha Swamy Temple Tipu sultan one of the most politically perceptive and tragic figures in modern Indian history In the play he had four dreams but in history has 37 dreams
Keywords: dreams; biblitheque; ramzan; khusrawi; busd; white elephant; thamari; dalw